Study on evaporation drainage of deep coal seam gas wells - Zhu, Hongying; Jing, Chuankai; Zhang, Fenna; Qi, Yaoguang; Hu, Hao; Yi, Tiantian (Frontiers in Energy Research, 2024)
Targeting the problem with small amounts of liquid loading during the flowing production of coal gas wells, which seriously affect the stable gas production of coal seam gas(CSG)wells. A model for water evaporation under high-pressure was established based on the Dalton evaporation law. The validation of the evaporation model was completed through experiments. By case analysis of CSG wells in the western edge of the Ordos Basin, the influence of different factors on the evaporation drainage capacity of CSG wells was analyzed. The results show that temperature and pressure have a significant impact on evaporation drainage. Increasing the gas production and temperature can significantly improve the drainage by evaporation. The initial moisture content of gas in the reservoir affects the ability of gas to absorb water vapor at the bottom of the wells. The magnitude of the initial moisture content is inversely proportional to the ability to absorb water vapor. To improve the evaporation drainage of gas wells, the temperature of the well fluid should be increased and the bottomhole flow pressure(BHFP) should be decreased. As a result, this will effectively prolong the flowing production time of CSG wells and reduce the costs of production.